IoT-Based Remote Patient Monitoring Systems in Healthcare: A Systematic Literature Review - Baz Mohammad Saifi; Amir Kror Shahidzay (Department of Informatics, Universitas Malikussaleh, 2026)
The Internet of Things (IoT) has emerged as a transformative technology in modern healthcare systems, particularly in enabling Remote Patient Monitoring (RPM). IoT-based RPM systems facilitate continuous real-time monitoring of patients through wearable sensors, communication networks, and cloud-based platforms, thereby improving healthcare accessibility and quality of care. This study aims to systematically review and synthesize the existing literature on IoT-based Remote Patient Monitoring systems, focusing on their architectures, application domains, benefits, challenges, research trends, and future directions. A systematic literature review methodology was adopted to identify relevant studies from major scientific databases, including IEEE Xplore, SpringerLink, PubMed, ScienceDirect, and Google Scholar. The search covered publications from 2020 to 2025. A total of 573 articles were initially identified, and 35 studies meeting the predefined inclusion criteria were selected for final analysis. The selected studies were analyzed across multiple dimensions, including system architectures, application domains, benefits, challenges, and emerging research trends. The findings indicate that IoT-based RPM systems significantly improve healthcare delivery by enabling continuous real-time monitoring, enhancing patient outcomes, and reducing healthcare costs. However, several challenges remain, including interoperability issues, wearable device energy consumption, data security and privacy concerns, and sensor reliability. Emerging trends include the integration of artificial intelligence, edge computing, and blockchain technologies into healthcare IoT systems. This review identifies several important research gaps, including the lack of standardized frameworks, limited real-world implementation, and insufficient focus on low-resource healthcare environments. The findings provide valuable insights for researchers and practitioners and offer guidance for future research aimed at developing secure, scalable, and efficient IoT-based healthcare systems.